Myocardial Bmp2 gain causes ectopic EMT and promotes cardiomyocyte proliferation and immaturity - Prados, Belén (Cell Death Dis, 2018)
During mammalian heart development, restricted myocardial Bmp2 expression is a key patterning signal for atrioventricular canal specification and the epithelial–mesenchyme transition that gives rise to the valves. Using a mouse transgenic line conditionally expressing Bmp2, we show that widespread Bmp2 expression in the myocardium leads to valve and chamber dysmorphogenesis and embryonic death by E15.5. Transgenic embryos show thickened valves, ventricular septal defect, enlarged trabeculae and dilated ventricles, with an endocardium able to undergo EMT both in vivo and in vitro. Gene profiling and marker analysis indicate that cellular proliferation is increased in transgenic embryos, whereas chamber maturation and patterning are impaired. Similarly, forced Bmp2 expression stimulates proliferation and blocks cardiomyocyte differentiation of embryoid bodies. These data show that widespread myocardial Bmp2 expression directs ectopic valve primordium formation and maintains ventricular myocardium and cardiac progenitors in a primitive, proliferative state, identifying the potential of Bmp2 in the expansion of immature cardiomyocytes.